2013
DOI: 10.1155/2013/283025
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factor Analysis and Microbial Etiology of Surgical Site Infections following Lower Segment Caesarean Section

Abstract: Background. Lower segment caesarean section (LSCS) is a common mode of delivery now and surgical site infection is the second most common infectious complication in these patients. This study was planned with this background to have a comprehensive approach to SSI following LSCS. Methods. 500 consecutive patients undergoing LSCS, irrespective of indication, were studied. A questionnaire was developed to assess the risk factors associated with development of SSI. All patients were followed up from day one of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
50
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 27 publications
11
50
6
1
Order By: Relevance
“…Another study carried out by Motie MR et al [3] with a mean age of 47.13 years with a SD of 19.60 years for the study group showed that most infections were cleancontaminated (46.3% ) and 30.5% contaminated as compared to 27.9% clean-contaminated and 43.1% contaminated in our study group. The length of surgery and type of surgery were found to increase the risk of SSIs in their study which is consistent with the results of our [17] study group carried out on women undergoing lower segment caesarian section showed an infection rate of 24.2% and the most common microorganism isolated was Acinetobacter (32.03%) followed by Escherichia coli and Klebsiella species responsible for 18.75% and 14.8% of SSIs, respectively. This is in contrast to our study where Staphylococcus was the main causative microorganism with incidence rate of SSIs caused by it was 25.7% and the overall incidence of SSIs was about 11%.…”
Section: Discussionsupporting
confidence: 88%
“…Another study carried out by Motie MR et al [3] with a mean age of 47.13 years with a SD of 19.60 years for the study group showed that most infections were cleancontaminated (46.3% ) and 30.5% contaminated as compared to 27.9% clean-contaminated and 43.1% contaminated in our study group. The length of surgery and type of surgery were found to increase the risk of SSIs in their study which is consistent with the results of our [17] study group carried out on women undergoing lower segment caesarian section showed an infection rate of 24.2% and the most common microorganism isolated was Acinetobacter (32.03%) followed by Escherichia coli and Klebsiella species responsible for 18.75% and 14.8% of SSIs, respectively. This is in contrast to our study where Staphylococcus was the main causative microorganism with incidence rate of SSIs caused by it was 25.7% and the overall incidence of SSIs was about 11%.…”
Section: Discussionsupporting
confidence: 88%
“…The wound swabs were sent at the time of admission and the common organisms; patients were given standard wound care, oral antibiotics and correction of co-morbidities along with supportive therapy. All analysis was carried out using the statistical software SPSS version 16 3,4,6 One of the patient related factors is young maternal age as most of the infections (92%) occurred in women less than thirty years of age, this is in accordance with other studies. 7,8 Hypertensive disorders in pregnancy which is linked with chronic alteration in peripheral blood supply have been found to a risk factor for SSI.9, 10 In this study 27.7% of patients with SSI suffered from this condition.…”
Section: Methodssupporting
confidence: 72%
“…This is in accordance with other studies elsewhere. 15,16 This could be due to the simple reason that emergency procedures are mostly unplanned and associated with other risk factors like prolonged membrane rupture, multiple vaginal examinations and prolonged labor. Antibiotic prophylaxis is one of the most significant protective factors in decreasing SSI.…”
Section: Methodsmentioning
confidence: 99%
“…In present study 48% of the patients had anemia which is consistent with Devjani et al study. 11 Poor control of glucose during surgery and in the perioperative period increases the risk of infection and worsens outcome of sepsis. The results of present study are consistent with Olsen MA et al study.…”
Section: Discussionmentioning
confidence: 99%